Specyfic pathological conditions of people buried at earlier Polish cementaries - Gładykowska-Rzeczycka, Judyta (Anthropological Review, 1982)
A brief outline of the role played by some specific ailments of importance for human history is given by the present author. The article deals more specifically with those pathologies which are frequent in skeletal material excavated at ancient cemeteries. Description of cases hitherto revealed on Polish skeletal materials is presented. The cases comprise 8 instances of bone tuberculosis (5 of the vertebral column and 3 of major joints — hip and knee), one case of lepra, syphilis and poliomyelitis. These two last cases are diagnosed tentatively only. Material and results are presented in the table 1. Table 2 presents numbers of vertebrae, innominate bones, femora and tibiae found in order to allow for correct interpretation of frequency of pathological cases. Data in both tables pertain to the same cemeteries.